STATEMENT PROCEDURES FOR DECLINE INCREASING IN BEKASI KAJIAN KEMACETAN TERHADAP PENURUNAN PENDAPATAN SUPIR ANGKOT DI BEKASI - Deslida Saidah; Mustika Sari; Danang Darunanto (Institut Transportasi dan Logistik Trisakti, 2017)
The purpose of this research is to know the cause of traffic jam in Bekasi high and urban transportation (angkot) not orderly passing, sharp decrease to income of Angkot in Bekasi. This research uses descriptive qualitative method with data analysis technique using interview, observation, documentation and triangulation of source. The result of the research, the very high traffic jam in Bekasi is caused by the number of city transportation exceeds the ideal amount, the increase of private vehicles especially motorcycle and road construction such as tolls and housing, flood. The angkot drivers are not orderly in Bekasi because of the chase of the deposit and the lack of angkot passengers and the replacement of the main public transportation drivers, the absence of officers in crowded places such as stations, shopping areas and the lack of strict officers. Revenue angkot very less because of the many rivals such as online-based vehicles, employee buses, school buses and motorcycles.